2006
DOI: 10.1152/physiolgenomics.00288.2005
|View full text |Cite
|
Sign up to set email alerts
|

BN phenome: detailed characterization of the cardiovascular, renal, and pulmonary systems of the sequenced rat

Abstract: Editor-in-Chief, Physiological Genomics. BN phenome: detailed characterization of the cardiovascular, renal, and pulmonary systems of the sequenced rat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 28 publications
1
26
1
Order By: Relevance
“…Blood was obtained at the moment of tissue collection by heart puncture after fasting overnight. Measurement of plasma glucose, serum cholesterol, and triglyceride concentrations were performed by Marshfield Laboratories (Marshfhield, WI) as described previously (8). Plasma glucose levels were measured by standard procedures as described (4).…”
Section: Blood Analysismentioning
confidence: 99%
“…Blood was obtained at the moment of tissue collection by heart puncture after fasting overnight. Measurement of plasma glucose, serum cholesterol, and triglyceride concentrations were performed by Marshfield Laboratories (Marshfhield, WI) as described previously (8). Plasma glucose levels were measured by standard procedures as described (4).…”
Section: Blood Analysismentioning
confidence: 99%
“…Mattson et al (26) have previously done a strain comparison of BN and FHH renal parameters and reported that BN rats are more resistant to the development of proteinuria and renal injury than FHH rats and that substitution of chromosome 1 from BN to FHH rats ameliorates renal injury in FHH.1BN consomic rats. Similarly, a study comparing BN to 10 other normotensive and hypertensive rat strains found that albumin and protein excretion, blood urea nitrogen (BUN), and plasma creatinine are significantly lower in BN than in FHH and Dahl S rats (23). Moreover, the BN rat was simply used as a donor strain for the 2.4-Mbp region of interest on RNO1.…”
Section: F573 Impaired Mr In Fhhmentioning
confidence: 99%
“…For example, Brown Norway (BN) rats exhibit more resistance to myocardial IR injury than does the Dahl saltsensitive (SS) strain (3). Moreover, introgression of BN chromosome 6 into an SS background (SS 6BN ) conferred significant cardioprotection (17). In other words, one or more genes on chromosome 6 with or without linkage to other chromosomes may be responsible for higher IR tolerance.…”
mentioning
confidence: 99%